The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/1348-0421.12581
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiles of pulmonary innate immune responses to isogenic antibiotic‐susceptible and multidrug‐resistant Pseudomonas aeruginosa

Abstract: The virulence of an isogenic pair of Pseudomonas aeruginosa strains was studied under similar experimental conditions in two animal infection models. The time to death was significantly longer for the multidrug resistant (MDR) than the wild-type strain. The transcriptional profiles of 84 innate immune response genes in the lungs of immune competent Balb/C mice were further compared. Significantly weaker expression of genes involved in production of soluble pattern recognition receptor and complement were obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…An earlier study [37] correlated the cytokine levels and bacterial clearance during an intraperitoneal infection in mice with MDR and sensitive isolates, along with reference strains of P. aeruginosa, and found that MDR strains induced a greater immune response that was able to effectively clear the infective bacteria at 12 h post-infection (p.i.). This suggested the presence of a fitness trade-off that compromises the pathogenic potentials and virulence of MDR isolates [38]. A previous study analyzing different mechanisms of antibiotic resistance that occur in clinical isolates of P. aeruginosa, causing severe bloodstream infections, concluded that acquisition of resistance did not lead to decreased fitness [39], and this correlated well with observations of enhanced survival of MDR-PA in infected cells that were made in our study too.…”
Section: Discussionsupporting
confidence: 90%
“…An earlier study [37] correlated the cytokine levels and bacterial clearance during an intraperitoneal infection in mice with MDR and sensitive isolates, along with reference strains of P. aeruginosa, and found that MDR strains induced a greater immune response that was able to effectively clear the infective bacteria at 12 h post-infection (p.i.). This suggested the presence of a fitness trade-off that compromises the pathogenic potentials and virulence of MDR isolates [38]. A previous study analyzing different mechanisms of antibiotic resistance that occur in clinical isolates of P. aeruginosa, causing severe bloodstream infections, concluded that acquisition of resistance did not lead to decreased fitness [39], and this correlated well with observations of enhanced survival of MDR-PA in infected cells that were made in our study too.…”
Section: Discussionsupporting
confidence: 90%
“…For example, ICU patients infected with extensively drug-resistant (XDR) P. aeruginosa presented elevated amounts of IL-10 in blood, as compared to patients infected with non-MDR P. aeruginosa ( Gomez-Zorrilla et al, 2017b ). Same result was obtained in a mouse model of P. aeruginosa pneumonia ( Tam et al, 2018 ). Consistently, patients infected with MDR M. tuberculosis presented higher amounts of IL-10 in the serum, as compared to patients infected with non-MDR M. tuberculosis ( Pinheiro et al, 2013 ).…”
Section: Mdr and Non-mdr Bacteria Induce Differential Il-10 Productiosupporting
confidence: 72%
“…Studies have shown an elevated amount of IL-10 in MDR P. aeruginosa –induced sepsis as compared with non-MDR P. aeruginosa infection in sepsis patients, as well as in a mouse model of P. aeruginosa pneumonia. 3 , 26 It has also been suggested that IL-10 in response to Mycobacterium tuberculosis infection, may downregulate the immune response and limit tissue injury, but overexpression of these cytokines may have a negative impact on the capacity to control infection. 27 Some studies have also shown that, in patients with human immunodeficiency virus infection 28 , 29 and other experimental infections, 30 – 32 high levels of IL-6 correlated with susceptibility to the pathogen and the disease severity of associated diseases.…”
Section: Discussionmentioning
confidence: 99%